Recognizing Bronchobiliary Fistula after Hepatic Ablation: A Distinct Clinical Syndrome and Its Multimodal Management - Yingjun Bao; Yuan Zhang; Diwen Zhu; Junpeng Gu; Weixin Ren (The American Surgeon™, 2026)
Background Bronchobiliary fistula (BBF) is a rare but significant complication of hepatic ablation, particularly in tumors adjacent to the diaphragm. With increasing use of thermal ablation, a growing literature has emerged characterizing its presentation and management. Methods We present a representative case of recurrent BBF after radiofrequency ablation for hepatocellular carcinoma, successfully managed with a multimodal interventional radiology approach. Following PRISMA guidelines, we conducted a systematic review of the literature on BBF after hepatic ablative therapy published between March 2005 and February 2026, identifying 20 eligible articles encompassing 39 cases. Results The pooled analysis revealed a distinct clinical syndrome: subphrenic tumor location (89.7%), delayed presentation at a median of 4-8 weeks post-ablation, and bilioptysis as the hallmark symptom (92.3%). Diagnostic strategies included CT, bronchoscopy, and cholangiography, often used in combination. Multimodal minimally invasive approaches, including percutaneous, endoscopic, and bronchoscopic techniques, account for 87.2% of current management. While interventional radiology–guided embolization achieved overall success in 66.7% of cases in this pooled series, it often required multiple sessions, reflecting the challenging nature of this complication. Based on these findings, we propose a practical treatment algorithm. Conclusion BBF after hepatic ablation follows a recognizable pattern that should prompt early diagnosis. A persistent, multimodal minimally invasive approach can achieve definitive closure in many cases and should generally be considered before proceeding to surgical intervention. The available evidence, however, remains limited to case reports and small series, and recommendations for specific embolization strategies should be interpreted with this in mind.